2023
DOI: 10.1002/ange.202310234
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐Induced Isomerization of Prenucleation Clusters During the Prenucleation Stage of CdTe Quantum Dots

Abstract: The evolution of prenucleation clusters in the prenucleation stage of colloidal semiconductor quantum dots (QDs) has remained unexplored. With CdTe as a model system, we show that substances form and isomerize prior to the nucleation and growth of QDs. Called precursor compounds (PCs), the prenucleation clusters are relatively optically transparent and can transform to absorbing magic‐size clusters (MSCs). When a prenucleation‐stage sample at 25, 45, or 80 °C is dispersed in a mixture of cyclohexane (CH) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 72 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…For CdTe, it is shown that PC-371 isomerizes to PC-448 via PC-417 in the reaction of Cd(OAc) 2 /OLA (made from cadmium acetate and oleylamine) + TeTOP (tri- n -octylphosphine telluride) + HPPh 2 in OLA (Figure S1B). Until the present study, the PC-to-PC isomerization in the reaction has not been demonstrated for CdS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For CdTe, it is shown that PC-371 isomerizes to PC-448 via PC-417 in the reaction of Cd(OAc) 2 /OLA (made from cadmium acetate and oleylamine) + TeTOP (tri- n -octylphosphine telluride) + HPPh 2 in OLA (Figure S1B). Until the present study, the PC-to-PC isomerization in the reaction has not been demonstrated for CdS.…”
mentioning
confidence: 99%
“…17 While those of calcium carbonate are "ionic polymers", 18 the ME prenucleation clusters are "covalent inorganic polymers". 19 They can transform into MSCs that have characteristic optical absorption; thus, they are called precursor compounds (PCs) of MSCs. Compared with their counterpart MSCs, PCs are relatively disordered with different electronic structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth fundamental understanding of the nucleation and growth of QDs should be able to provide guidelines for better design and synthesis. Thanks to the noninjection-based approach, , a reaction can be readily stopped in the prenucleation stage, which is almost impossible for the injection-based approach. , Prenucleation clusters that are relatively transparent in optical absorption were trapped. They form via chemical self-assembly, that occurs prior to nucleation and growth of QDs. These prenucleation clusters can transform to magic-size clusters (MSCs) and QDs. Thus, a multistep nonclassical model should be taken into account to understand the nucleation and growth of colloidal QDs, instead of the one-step classical LaMer model . It is highly possible that MSCs and QDs are regulated differently in relation to quantum size effects because shape comes into play for the former. ,, On a side note, CdSe MSCs (with a size of ∼1.2 nm and optical absorption peaking at ∼415 nm) were produced in the hot-injection approach; the bandwidth of MSCs is narrower due to the almost complete absence of size distribution.…”
mentioning
confidence: 99%
“…An in-depth fundamental understanding of the nucleation and growth of QDs should be able to provide guidelines for better design and synthesis. Thanks to the noninjection-based approach, 24 , 25 a reaction can be readily stopped in the prenucleation stage, 26 28 which is almost impossible for the injection-based approach. 5 , 23 Prenucleation clusters that are relatively transparent in optical absorption were trapped.…”
mentioning
confidence: 99%